Nitro-Grela-type complexes containing iodides – robust and selective catalysts for olefin metathesis under challenging conditions - Tracz, Andrzej; Matczak, Mateusz; Urbaniak, Katarzyna; Skowerski, Krzysztof (Beilstein Journal of Organic Chemistry, 2015)
Iodide-containing nitro-Grela-type catalysts have been synthesized and applied to ring closing metathesis (RCM) and cross metathesis (CM) reactions. These new catalysts have exhibited improved efficiency in the transformation of sterically, non-demanding alkenes. Additional steric hindrance in the vicinity of ruthenium related to the presence of iodides ensures enhanced catalyst stability. The benefits are most apparent under challenging conditions, such as very low reaction concentrations, protic solvents or with the occurrence of impurities.
Keywords: green solvents; macrocyclization; metathesis; ruthenium